Life is sweet - Bass, Elizabeth, 1965- (Kensington Books, 2014)
Three years ago, Becca Hudson threw a dart at a map, hit Leesburg, Virginia, and decided it was the perfect place to start over. Now she has her own bakery, The Strawberry Cake Shop, loyal customers, and close friends. She also has something that success as a Hollywood child star couldn't give her: a mostly normal existence. Not that it's without complications. One best friend, Pam, is in the wary early days of a new relationship; another is fighting to save her marriage in the midst of infidelity. And then there's Becca's growing attraction to Matthew, surrogate stepdad to Olivia, a smart, sensitive ten-year-old who's become a fixture in the bakery and in Becca's affections.